Direct comparison of the flame inhibition efficiency of transition metals using metallocenes. (April 2015) - Koshiba, Yusuke; Agata, Saori; Takahashi, Tomohide; Ohtani, Hideo
Abstract: This study aimed to directly and systematically compare the flame inhibition abilities of various transition metals, including vanadium, ruthenium, osmium, chromium, manganese, iron, cobalt, and nickel, by using the corresponding metallocenes: vanadocene, ruthenocene, osmocene, chromocene, manganocene, ferrocene, cobaltocene, and nickelocene. The downward flame spread rates over filter paper samples on which each metallocene was adsorbed were measured. In addition, thermogravimetric measurements were carried out to finally determine the phase in which each metallocene produced its flame inhibition effect. The results indicated that all these metallocenes, with the exception of vanadocene, exhibit a flame inhibition effect solely in the gas phase, whereas vanadocene shows fire suppression ability in the solid phase. This work also found that, in terms of their fire suppression abilities, the transition metals can be ranked in the following order: Cr>Mn>Fe>Co>Ni>(V>)Os>Ru. Highlights: The flame inhibition effects of transition metals are evaluated using metallocenes. Solid phase inhibition efficiencies are determined by thermogravimetric analysis. The abilities of the metals can be ranked as: Cr>Mn>Fe>Co>Ni>(V>)Os>Ru.